2021
DOI: 10.21203/rs.3.rs-763052/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Five-Level Unilateral Laminectomy Bilateral Decompression (ULBD) by Two-Stage Unilateral Biportal Endoscopy (UBE)

Abstract: Background Unilateral biportal endoscopy (UBE) is a relatively new yet common minimally invasive procedure in spine surgery, capable of achieving adequate decompression for lumbar spinal stenosis through unilateral laminectomy bilateral decompression (ULBD). Neither additional fusion nor rigid fixation is required, as UBE-ULBD rarely causes iatrogenic lumbar instability. However, to our knowledge, five-level ULBD via two-stage UBE without lumbar fusion has been yet to be reported in the treatment of multilevel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A significant advantage of UBE over PELD/PEID lied in its utilization of two channels instead of pipes, providing enhanced operational flexibility with freely adjustable angles. Substantial evidence indicated that UBE exhibited a relatively short learning curve, ensuring the safe performance of the procedure [25,26]. Moreover, when compared with the PELD, UBE closely resembled open discectomy, a method familiar to spinal surgeons.…”
Section: Advantages and Disadvantages Of Ube Compared With Uniportal ...mentioning
confidence: 99%
“…A significant advantage of UBE over PELD/PEID lied in its utilization of two channels instead of pipes, providing enhanced operational flexibility with freely adjustable angles. Substantial evidence indicated that UBE exhibited a relatively short learning curve, ensuring the safe performance of the procedure [25,26]. Moreover, when compared with the PELD, UBE closely resembled open discectomy, a method familiar to spinal surgeons.…”
Section: Advantages and Disadvantages Of Ube Compared With Uniportal ...mentioning
confidence: 99%